Implementasi manajemen pengetahuan menggunakan model SECI di Perpustakaan Universitas Islam Negeri Walisongo Semarang - Nugraheni, Nurul; Bakhri, Syaiful; Alam, Umar Falahul; Ahwan, Muh Ahlis (Daluang: Journal of Library and Information Science, 2024)
Purpose. This research aims to determine knowledge management using the SECI Model in the UIN Walisongo Library and determine the obstacles in implementing knowledge management in the UIN Walisongo Semarang Library.Methodology. This research uses qualitative research methods with data collection techniques through interviews, field observations, and documentation from the library. Researchers conducted interviews with the head of the library, librarians and several students. Data validity techniques use source triangulation and method triangulation. The data analysis techniques used are: data reduction, data presentation, drawing conclusions.Results and discussion. The results and discussion of this research show that, 1) Management knowledge at the UIN Walisongo Semarang Library using SECI model analysis including the socialization stage carried out in internal & external libraries, externalization stage includes writing and library service innovation, combination stage includes organizing catalogs, repositories, and documents, stages Internalization includes workshop activities, benchmarking, and seminar. 2) Barriers to implementing knowledge management in There are two factors in the UIN Walisongo library, namely factors internal and external libraries.Conclusions. UIN Walisongo Semarang Library uses the SECI model in managing knowledge (socialization, externalization, combination, internalization) but faces challenges such as diverse individual abilities, lack of librarians and no regeneration, as well as low awareness of student knowledge documentation and information literacy. The recommendations include encouraging knowledge exchange between staff, developing social media innovations to facilitate access, and contributing to library and information science studies to increase digital era literacy and maximize library services.